Bibliometrics Analysis of Research Publications Related to Sus scrofa domesticus - Muhammad Najmi Mohammad Fauzi; Abdul Syakur Aqil Mat Anuar; Irfan Ezani Shuhaimi; Nur Fazidah Asmuje@Asmuzi; Tg Ainul Farha Tg Abdul Rahman; Nurdalila A’wani Abdul Aziz (USIM Press, 2024)
Vol. 5 No. 2 (2020): Jurnal Sains Insani